以准双曲面锥齿轮研齿运动参数为核心的数控化探究与实施 - 闫花茹; 田长留; 张华 (Jixie chuandong)
As a precise machining process,traditional lapping cannot meet the demand of highly socialized mass production.For high efficiency and high quality,lapping technology of NC to lapping motion parameters as core is researched for hypoid gear.Elastic and grating devices are additionally set up for tooth contact on rolling.With its actual measurement and theoretical deduction,the accurate lapping motion parameters can be obtained by calling MatLab calculation program under VC++,and the automatic lapping and motion control programs are designed,which takes an important step in precise control for lapping on tooth surface and development of NC of lapping tooth machine for hypoid gears.